Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1080/01635589809514737
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin and liver cancer in Sudan

Abstract: This study investigated whether aflatoxin contamination of peanut products may contribute to the incidence of hepatocellular carcinoma (HCC) in Sudan. Thirty-seven peanut butter and peanut samples were collected from local markets. Aflatoxin concentrations were significantly higher in West Sudan [87.4 +/- 197.3 (SD) micrograms/kg], a high-risk area, than in Central Sudan (8.5 +/- 6.8 micrograms/kg), a low-risk area. In West Sudan, humid local storage conditions of peanut products were related to high aflatoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…However, most studies of aflatoxin/HBV interactions were limited in evaluating joint effects since the populations studied consisted almost exclusively of HBV carriers Wang et al, 1996;Sun et al, 1999). Previous studies in Africa are limited to ecological studies comparing regional HCC rates to estimated aflatoxin intake (Autrup et al, 1987;Omer et al, 1998;van Rensburg et al, 1990). Three small case-control studies of HCC in Africa have assessed aflatoxin exposure at the individual level, with equivocal results (Olubuyide et al, 1993;Mandishona et al, 1998;Omer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies of aflatoxin/HBV interactions were limited in evaluating joint effects since the populations studied consisted almost exclusively of HBV carriers Wang et al, 1996;Sun et al, 1999). Previous studies in Africa are limited to ecological studies comparing regional HCC rates to estimated aflatoxin intake (Autrup et al, 1987;Omer et al, 1998;van Rensburg et al, 1990). Three small case-control studies of HCC in Africa have assessed aflatoxin exposure at the individual level, with equivocal results (Olubuyide et al, 1993;Mandishona et al, 1998;Omer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mutegi et al (2012) reported A. flavus L-strain, A. flavus S-strain, and A. niger as the major fungal pathogens infecting groundnuts and groundnut products from Busia and Homa Bay districts in Western Kenya. Aspergillus flavus and aflatoxin have been reported in groundnuts in Sudan (Omer, 2001;Omer et al, 2001) and Egypt (Abdelhamid, 1990) and in peanut butter in Sudan (Eshafie et al, 2011).Aspergillus flavus, the main producer of aflatoxin, only grows in groundnuts when the moisture content exceeds 9% and has optimum growth conditions of between 25 and 30 o C, and water activity of 0.99 with a minimum of 0.83aw, while production of aflatoxin occurs optimally at 25 o C and 0.99aw with a minimum of 0.87aw (Ribeiro et al, 2006). The warm and humid environmental conditions in Africa are ideal for growth of A. flavus making aflatoxin contamination of food, including groundnuts, a widespread problem across the continent (Gordon, 2003;Bankole et al, 2006;Wagacha & Muthomi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Peanut butter consumption conferred no increased risk in central Sudan, but a very high risk in western Sudan (OR in the highest quartile, 8.7). Aflatoxin contamination of peanut butter was found to be a much greater problem in western Sudan than in central Sudan (Omer et al, 1998). The authors also noted, however, that residents of the two regions are ethnically different, so effect modification by unmeasured genetic or environmental factors cannot be excluded.…”
Section: Case-control Studiesmentioning
confidence: 95%
“…Thus, the very different types of analysis all pointed to an association between urinary AF and HCC. Omer et al (1998) carried out a comparison of AF contamination of peanut products in two areas of Sudan. The study was carried out in 1995 and involved selection of peanut butter samples from local markets using a staged sampling approach to identify markets in the two study areas.…”
Section: Ecological and Cross-sectional Studiesmentioning
confidence: 99%